WORK FROM ANYWHERE, HYBRID, AND FLEXIBLE WORKING IN THE CIVIL SERVICE: GLOBAL BIBLIOMETRIC TRENDS AND POLICY IMPLICATIONS FOR INDONESIA - Hakim, Arif Rahman; Wijaya, Berta Margareta Agustin (Universitas Pakuan, 2025)
ABSTRACTFlexible work arrangements, such as working from anywhere, remote work, hybrid work, and flexible working, have rapidly expanded in the public sector since the COVID-19 pandemic. This study aims to map global research trends on flexible work in the public sector and examine their managerial implications. The population consists of global scholarly publications on flexible work in the public sector indexed in Scopus. The sample includes 64 journal articles published between 2010 and 2025, selected using the PRISMA protocol. Data were analyzed using bibliometric techniques in VOSviewer and Biblioshiny, and interpreted through the Job Demands–Resources and Sociotechnical Systems perspectives. The findings show a significant rise in publications after 2020 with dominant themes related to productivity, digital transformation, hybrid work, and employee well-being. The results also reveal limited exploration in emerging country contexts. These findings imply the need to strengthen digital readiness, output-based performance systems, and employee engagement in implementing flexible work arrangements. This study contributes by providing an evidence-based framework to support sustainable flexible work strategies in the public sector.ABSTRAKPengaturan kerja fleksibel seperti work from anywhere, remote work, hybrid work, dan flexible working semakin berkembang di sektor publik sejak pandemi COVID-19. Penelitian ini bertujuan untuk memetakan tren riset global mengenai kerja fleksibel di sektor publik serta mengkaji implikasi manajerialnya. Populasi penelitian ini adalah publikasi ilmiah global mengenai kerja fleksibel di sektor publik yang terindeks Scopus. Sampel penelitian terdiri dari 64 artikel jurnal periode 2010–2025 yang dipilih menggunakan protokol PRISMA. Analisis data dilakukan dengan teknik bibliometrik melalui VOSviewer dan Biblioshiny serta diinterpretasikan menggunakan perspektif Job Demands–Resources dan Sociotechnical Systems. Hasil penelitian menunjukkan peningkatan signifikan dalam publikasi setelah tahun 2020 dengan tema dominan terkait produktivitas, transformasi digital, kerja hibrida, dan kesejahteraan pegawai. Temuan juga menunjukkan masih terbatasnya eksplorasi konteks negara berkembang. Implikasi penelitian ini menekankan pentingnya penguatan kesiapan digital, sistem kinerja berbasis output, dan keterikatan pegawai dalam implementasi kerja fleksibel. Studi ini berkontribusi dengan menyediakan kerangka berbasis bukti untuk mendukung strategi kerja fleksibel yang berkelanjutan di sektor publik.